2007
DOI: 10.1111/j.1749-7345.2005.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Black Tiger Shrimp Penaeus monodon Spermatophores by Chilled Storage

Abstract: Chilled storage of spermatozoa in fish has been extensively investigated for many years, but limited research was focused on crustacean species. Chilled storage of spermatophores of black tiger shrimp Penaeus monodon is needed to generate consistent and reliable supply of spermatozoa for subsequent use. The objective of this study was to develop a protocol for the chilled storage of black tiger shrimp spermatophores and to evaluate bacterial propagation during chilled storage of spermatophores. In the first ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…In both the trials, spawned eggs were lysed after 6 h, and only with unused fresh seawater was it possible to obtain shrimp nauplii (with an apparent hatching rate of 91.7–92.9%). A similar hatching rate was obtained by Babu et al (2001) and Nimrat et al (2005). Van Wyk and Scarpe (1999) found that the ratio of the divalent ions (Ca +2 and Mg +2 ) to the monovalent ions (Na+ and K+) is critical for shrimp reared at a low salinity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In both the trials, spawned eggs were lysed after 6 h, and only with unused fresh seawater was it possible to obtain shrimp nauplii (with an apparent hatching rate of 91.7–92.9%). A similar hatching rate was obtained by Babu et al (2001) and Nimrat et al (2005). Van Wyk and Scarpe (1999) found that the ratio of the divalent ions (Ca +2 and Mg +2 ) to the monovalent ions (Na+ and K+) is critical for shrimp reared at a low salinity.…”
Section: Discussionsupporting
confidence: 82%
“…The next day at 08:00 hours, females were returned to their original tanks (Peixoto et al 2005; Gandy et al 2007). The spawning rate and apparent hatching rate were evaluated using the procedure described by Huang, Jiang, Lin, Zhou and Le (2008) and Nimrat, Sangnawaiuj and Vuthiphandchai (2005) respectively. Random samples from the spawning tank were used to determin the quality and total egg numbers (Babu, Kitto, Ravi & Marian 2001; Peixoto et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, simultaneous handling of many samples makes it difficult the execution of each step in optimal time conditions, generating a range of results in cryopreservation studies. Finally, emphasis should be given to the fact the limited success obtained in many species of penaeidae reproduction in captivity could be related with reproductive problems in the males, since most studies with shrimps describe females, a gap to be fulfilled with the development of studies concerning spermatophore production and sperm quality (Nimrat et al 2005) as well as of biotechnologies of assessment for sperm quality. In conclusion, there was no difference observed between the two cryoprotectants tested, DMSO and EG on results for cell survival, Cell viability decreased as storage time in liquid nitrogen increased and flow cytometry and eosine-nigrosine stain techniques were highly correlated, indicating that both could be used with high probability for confidence in the analyses of sperm cells viability.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium free saline is the most commonly used prawn sperm extender for sperm cryopreservation (Bart, Choosuk, & Thakur, ; Vuthiphandchai, Nimrat, Kotcharat, & Bart, ) or chilled sperm storage (Bray & Lawrence, ; Morales‐Ueno, Paniagua‐Chávez, Martínez‐Ortega, Castillo‐Juárez, & Alfaro‐Montoya, ) as the depletion of calcium typically prevents sperm AR in penaeid species. Alternative sperm extenders that have been reported include artificial crustacean haemolymph (Nimrat, Sangnawakij, & Vuthiphandchai, ; Talbot, Poolsanguan, Poolsanguan, & Al‐Hajj, ), natural seawater (Bray & Lawrence, ), phosphate buffer (Nimrat et al, ) and mineral oil (Nimrat et al, ). Within the spermatophore, there is a large volume of glutinous fluid covering the sperm mass, possibly providing extra protection for the embedded spermatozoa (Sasikala & Subramoniam, ); consequently, it may be prudent to examine whether sperm quality is affected by breaching the spermatophore wall, in which case the spermatozoa are either chilled preserved as a free sperm suspension or retained within the intact spermatophore.…”
Section: Introductionmentioning
confidence: 99%
“…Within the spermatophore, there is a large volume of glutinous fluid covering the sperm mass, possibly providing extra protection for the embedded spermatozoa (Sasikala & Subramoniam, ); consequently, it may be prudent to examine whether sperm quality is affected by breaching the spermatophore wall, in which case the spermatozoa are either chilled preserved as a free sperm suspension or retained within the intact spermatophore. With respect to prawn sperm storage time, a prolonged period of sperm storage, regardless of through cryopreservation or chilled storage, has been proven to have a negative impact on the sperm quality as assessed by fertility rate (Nimrat et al, ; Vuthiphandchai et al, ).…”
Section: Introductionmentioning
confidence: 99%